2021
DOI: 10.51383/ijonmes.2021.137
|View full text |Cite
|
Sign up to set email alerts
|

Classroom management of pre-service and beginning teachers: From dispositions to performance

Abstract: Classroom management is a central aspect of effective teaching. It is related to student motivation and learning achievement. Unfortunately, pre-service and beginning teachers lack on classroom management competence. Therefore, this study aims to find out, which classroom management facets pre-service and beginning teachers struggle with and how they are associated with each other. Professional knowledge, self-efficacy, professional vision, and performance of 206 pre-service and beginning teachers were measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 0 publications
0
9
1
1
Order By: Relevance
“…Notably, classroom management and strategies remain to be one of the imperative things that teachers need. This is supported by Junker et al (2021) who made mention about beginning teachers lacking classroom management competence. In their study, beginning teachers were found to be least prepared in effective classroom management.…”
Section: " (T9) "Ways Of Handling the Gen Z Learners Better And Susta...mentioning
confidence: 86%
“…Notably, classroom management and strategies remain to be one of the imperative things that teachers need. This is supported by Junker et al (2021) who made mention about beginning teachers lacking classroom management competence. In their study, beginning teachers were found to be least prepared in effective classroom management.…”
Section: " (T9) "Ways Of Handling the Gen Z Learners Better And Susta...mentioning
confidence: 86%
“…Firstly, it affords an invaluable opportunity to scrutinize and subsequently augment the competencies of PTs in the conveyance of information, both in asynchronous video lectures and traditional classroom settings. Research indicates that, as PTs progress in their professional trajectory, there is a propensity to prioritize classroom management skills over the refinement of information delivery techniques (Junker et al, 2021). This often results in a diminished focus on honing the skills necessary for effective knowledge transmission (e.g.…”
Section: Comparing Body Movement and Pointing In Teaching Between Pts...mentioning
confidence: 99%
“…According to Junker et al (2021), Classroom management is a central aspect of effective teaching. It is related to student motivation and learning achievement.…”
Section: (Ti9)mentioning
confidence: 99%